Post-valvular surgery multi-vessel coronary artery spasm — A literature review. (March 2016) - Formica, Francesco; Bamodu, Oluwaseun Adebayo; Mariani, Serena; Paolini, Giovanni
Abstract: Coronary artery spasm (CAS) refers to the spontaneous or stimuli-induced transient, often localized and intense subtotal or total constriction/occlusion of the epicardial coronary artery, usually concomitant with angina pectoris with associated elevation of the ST segment on electrocardiogram (ECG). In this article, we present a literature review on post-valvular surgery CAS and report the clinical case of a 77 year-old man who experienced severe early post-aortic surgery chest pain and hemodynamic instability. Emergent coronary angiography revealed severe occlusion of multiple branches of both coronary arteries. The CAS was alleviated with intracoronary infusion of nitroglycerin. Highlights: Postvalvular surgery coronary artery spasm (CAS) is a multifactorial, infrequent but lethal open heart surgery complication. Despite its multifactorial mechanistic underlining, there is no universal prophylactic or definitive treatment for CAS. CAS is a recognized culprit in perioperative agina, acute myocardial infarction and associated hemodynamic instability. Optimal therapeutic strategy for postoperative CAS continues to evolve. There is need for globally standardized diagnostic and therapeutic protocol, with continued research of CAS pathomechanism.